American Lamiinae (Coleoptera, Cerambycidae): new species of Acanthocinini and Hemilophini and a new synonymy in Cirrhicera Thomson - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2024)
Four new species are described: Lepturges (Lepturges) consimilis sp. nov. (Acanthocinini), from Costa Rica and Panama; Oedopeza raberi sp. nov. and Oedopeza hovorei sp. nov. (Acanthocinini), from Panama; and Cirrhicera vandenberghei sp. nov. (Hemilophini), from Guatemala. Cirrhicera panamensis Bates, 1885 is synonymized with C. sallei Thomson, 1857.